Generation of intense ultra-short X-ray pulses in wake field undulator - Opanasenko, A. (Вопросы атомной науки и техники, 2011)
The generation of X-rays based on the interaction mechanism of a relativistic charged particles with alternative wake fields induced in periodic structures are studied. The optimum wake field characteristics providing the maximum flux of wake field undulator radiation in an X-ray range are obtained. Using the data on beam parameters of varied photo-injector projects, the X-ray fluxes are calculated. Представлено результати дослідження процесу генерації рентгенівського випромінювання, заснованого на механізмі взаємодії заряджених частинок зі знакозмінними кільватерними полями, що індуковані у періодичних структурах. Знайдено оптимальні співвідношення між розмірами гофрованого хвилеводу та електронного згустка, при яких досягаються максимальні потоки випромінювання. Представлены результаты исследования процесса генерации рентгеновского излучения, основанного на механизме взаимодействия заряженных частиц со знакопеременными кильватерными полями, индуцируемыми в периодических структурах. Найдены оптимальные соотношения между размерами гофрированного волновода и размерами электронного сгустка, при которых достигаются максимальные потоки излучения.